Ranges of Evening Grosbeak (Hesperiphona vespertina) call types 1 and 2 documented from community science and targeted placement of automated recorders - Kirsch, William M.; Hahn, Thomas P.; Young, Matthew A.; Robinson, W. Douglas (Frontiers in Bird Science, 2026)
The Evening Grosbeak (Hesperiphona vespertina) is a species of North American Fringillid finch with at least five populations defined by differences in their flight calls. Groups with different flight calls generally occupy different geographic ranges during the breeding season and are referred to as call types. In Oregon and California, USA, call types 1 and 2 overlap in the Cascade and Sierra Nevada mountain ranges, but the geographical extent of this overlap remains unclear. We used citizen science data, our own ad hoc surveys, and a network of autonomous recording units (ARUs) across a longitudinal range from northern California into Oregon to quantify the distributions of these call type populations. We found a clear north-south transition, with type 1 birds occurring primarily in the northern sections of our study area while type 2 birds were predominantly detected in the Sierra Nevada mountains. Both types overlapped during the breeding season in southern Oregon. Both types also wandered widely after the breeding season and often co-occurred throughout the study area, especially in the Sierra Nevada. Type 2 was always rare north of southern Oregon. Additionally, our ARU data indicate greater occurrence of both call types where Evening Grosbeaks were most often recorded overall, especially after the breeding season. Our results align with Grinnell’s (1917) hypothesis of the presence of a contact zone between two populations of Evening Grosbeaks in Oregon and California and clarify the current extent of this geographic overlap.